1993
DOI: 10.1246/bcsj.66.2097
|View full text |Cite
|
Sign up to set email alerts
|

Archaebacterial Lipids: Stable Anionic Membranes from 1,2-Bis(dihydrophytyl)glycero-3-phosphate

Abstract: 1,2-Bis(dihydrophytyl)glycero-3-phosphate (DPhyPA) was synthesized as an analog of archaebacterial lipids. Upon sonicating in amine-containing buffers like 0.05 M Tris–HCl (pH 7.8), the lipid gave rise to the stable liposomal assemblies, which could store 5(6)-carboxyfluorescein at high temperature as high as 70 °C in the interior. The assembly also had a large negative zeta-potential and showed an absence of gel-to-liquid crystalline phase transition from −20 to 80 °C. A Langmuir monolayer at an air/water int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Two similar cases of vesicle formation induced by additives have been reported. [7c, 21] Synchrotron X-ray diffraction: We and others [11] have shown that the simplest phosphate 1 easily forms giant vesicles, however, the diffraction pattern unexpectedly showed well-expressed hexagonal structures over the entire temperature range measured (from 5 8C to 87 8C), with a distance between cylinders of 6.23 nm at 20 8C and 5.76 nm at 87 8C. This apparent contradiction, may be due to two differences: the synchrotron study was run at a 10 3 higher concentration of lipid, in pure water (pH 7) instead of a pH 7.8 ± 8.4 buffer.…”
Section: -Membered Macrocyclic Diphosphates 3abmentioning
confidence: 99%
See 1 more Smart Citation
“…Two similar cases of vesicle formation induced by additives have been reported. [7c, 21] Synchrotron X-ray diffraction: We and others [11] have shown that the simplest phosphate 1 easily forms giant vesicles, however, the diffraction pattern unexpectedly showed well-expressed hexagonal structures over the entire temperature range measured (from 5 8C to 87 8C), with a distance between cylinders of 6.23 nm at 20 8C and 5.76 nm at 87 8C. This apparent contradiction, may be due to two differences: the synchrotron study was run at a 10 3 higher concentration of lipid, in pure water (pH 7) instead of a pH 7.8 ± 8.4 buffer.…”
Section: -Membered Macrocyclic Diphosphates 3abmentioning
confidence: 99%
“…[9] We have previously shown that phosphates instead of phosphatidylcholines or other complex headgroups are efficient for membrane formation with polyprenyl derivatives, both with two chains [10a] or with only one, [10b] and we have hypothesized that these polyprenyl phosphates may have been the most primitive phospholipids. As diphytanylglyceryl phosphate 1 easily formed vesicles, [11] we now study the phosphates 3ab (X PO 3 H 2 , 1:1 mixture [molar] of 3 a and 3 b), 4 (X PO 3 H 2 ), and 5 (X PO 3 H 2 ).…”
Section: Introductionmentioning
confidence: 99%